2020
DOI: 10.3390/biom10071046
|View full text |Cite
|
Sign up to set email alerts
|

ProAKAP4 as Novel Molecular Marker of Sperm Quality in Ram: An Integrative Study in Fresh, Cooled and Cryopreserved Sperm

Abstract: To improve artificial insemination protocols in ovine species it is crucial to optimize sperm quality evaluation after preservation technologies. Emerging technologies based on novel biomolecules and related to redox balance and proteins involved in sperm motility such as ProAKAP4 could be successfully applied in ram sperm evaluation. In this work, a multiparametric analysis of fresh, cooled, and cryopreserved ram sperm was performed at different complexity levels. Samples were evaluated in terms of motility (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 70 publications
(110 reference statements)
7
37
2
Order By: Relevance
“…Jumeau et al (2018) stated that there was a positive correlation between the proAKAP4 level and the sperm motility of human spermatozoa separated from seminal plasma, detected using the SDS‐PAGE and protein immunoblot methods. Previous studies performed in stallion, ram, dog and bull frozen‐thawed semen samples reported a positive correlation between the proAKAP4 levels determined by ELISA and CASA techniques performed at hour 0 (post‐thawed) in terms of total motility, progressive motility, BCF, LIN, VCL and VSL (Blommaert et al., 2019; Le Couazer et al., 2019; Riesco et al., 2020; Ruelle et al, 2019). In addition to the CASA results, Ruelle et al (2019) stated that the correlation was associated with the success rates of approximately 200,000 AI practices to support their hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…Jumeau et al (2018) stated that there was a positive correlation between the proAKAP4 level and the sperm motility of human spermatozoa separated from seminal plasma, detected using the SDS‐PAGE and protein immunoblot methods. Previous studies performed in stallion, ram, dog and bull frozen‐thawed semen samples reported a positive correlation between the proAKAP4 levels determined by ELISA and CASA techniques performed at hour 0 (post‐thawed) in terms of total motility, progressive motility, BCF, LIN, VCL and VSL (Blommaert et al., 2019; Le Couazer et al., 2019; Riesco et al., 2020; Ruelle et al, 2019). In addition to the CASA results, Ruelle et al (2019) stated that the correlation was associated with the success rates of approximately 200,000 AI practices to support their hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…Probably this negative effect is due to some deleterious effects at the structural level since the sperm metabolism was not affected by the gentamicin respect to the C samples. A recent study carried out by Riesco et al ( 32 ) demonstrated a novel sperm protein (ProAKAP4) as a promising diagnostic parameter of sperm quality in ram sperm, so long correlated to sperm motility. This protein is the most expressed protein of the sperm fibrous sheath being an important part of the flagellum ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm samples of different experimental groups were diluted in phosphate-buffered saline (PBS) medium to obtain a total of 2 × 10 6 of spermatozoa per sample; these samples were centrifuged at 500× g for 10 min at RT. The flow cytometry staining protocol has been previously described by Riesco et al, 2020 [ 29 ]. Briefly, the supernatant was discarded and the sperm pellet was incubated at RT for 30 min in the dark with 96 μL of Zombie Violet™ (membrane integrity probe) (1:1000 final dilution in PBS, Biolegend, Madrid, Spain), 2 μL of CellEvent™ Caspase-3/7 (apoptosis marker) (4 μM final concentration in PBS, Thermo Fisher, Madrid, Spain) and 2 μL of CellROX ® (ROS content labeling) (5 μM final concentration in PBS, Thermo Fisher, Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%